THE INFLUENCE OF SERVICE QUALITY AND FACILITIES ON CUSTOMER SATISFACTION AT BERLIAN ABADI HOTEL BANYUWANGI - Nilawati, Wardha (CV. Radja Publika, 2022)
Abstract The service industry is currently experiencing very rapid development in line with the needs of the community for various types of services in various fields of life. The development of competition intensity and the number of competitors makes the company must always pay attention to the needs and desires of customers, and try to meet customer expectations by providing better service than competitors do. This research was conducted at Hotel Berlian Abadi Banyuwangi by taking 60 respondents who were hotel consumers. This study uses a questionnaire method and data processing uses questionnaire analysis, and data processing uses multiple linear regression analysis, F test, t test, and determination by first using the items in the questionnaire to test the validity of its reliability. Based on the results of the analysis, the SPSS program proved to be significantly correlated at the level of significance (sig <0.05) so that it was declared valid in the measurement. Reliable because the Cronbach Alpha value is ≥ 0.6. Based on the F test, the calculated F number is greater than the F table (76.136 > 3.16). Thus the rule of the F test decision states rejecting Ho and accepting Ha, which says there is a significant influence between service quality and facilities on customer satisfaction Hotel Berlian Abadi Banyuwangi. From the analysis using the classic heteroscedasticity assumption test, it is known that the variable quality of service (X1) and facilities (X2) are shown that the significance value is greater than (0.05) and t count <t table, it can be ascertained that the model does not contain heteroscedasticity.